Study of Seasoning Powder Processing from Gray Abalone Mushroom - Nhi Yen Thi Tran; Ngoc Vu Duc; Truong Dang Le; Long Bao Huynh; Anh Viet Van Nguyen; Tan Phat Dao (Journal of Food Quality)
The gray abalone mushroom is a rich source of amino acids and carbohydrate compounds, with some biological activities and antioxidants. Nowadays, the variety of food additives on the market such as sodium glutamate (E621), sodium guanylate (E627), or sodium insonate (E631), could probably cause negative effects for people’s health. This study used gray abalone mushrooms to create naturally derived seasoning products without using flavor enhancers and synthetic compounds. The gray abalone mushroom was pretreated and dried at 60°C until attaining the moisture content of <5%, while the biological activity and antioxidant values were kept optimal. The mixture ingredients, including 5% abalone mushroom powder, 2% baby cornstarch, and other seasoning ingredients, were uniformly ground. The based-gray abalone mushroom powder that was packed in PE with the moisture content below 3% displayed stability in terms of quality throughout 90 days. Gray abalone mushroom seasoning powder contributed to creating safe, natural products as well as improving consumers’ health.